Analisis Beban Kerja Fisik Bidan dengan Penerapan Patient Safety pada Masa Pandemi Covid-19 Di RSUD Kabupaten Bekasi Tahun 2021 - Mariyani, Mariyani (Ikatan Bidan Indonesia (IBI), 2023)
Background: Working in challenging conditions such as during the Covid-19 pandemic can have an impact on the ability of health workers to provide safe and effective care.Research Objectives: To determine the relationship between the physical workload of midwife and the application of patient safety during the Covid-19 pandemic at the Bekasi District Hospital in 2021.Research Methods: This study uses a quantitative approach with a cross sectional research design. The total population in this study were 94 respondents and the sampling technique was simple random sampling with a sample of 55 respondents. The instrument in this study is a questionnaire. The analysis used is univariate and bivariate analysis.Research results: From 55 respondents, it was found that the total physical workload of midwife was 33 people and midwife who implemented good patient safety were 11 people (33.3%), while the physical workload of midwife who were moderate was 19 people and midwife who implemented patient safety. there are 11 people (57.9%), and the physical workload of midwife who are light in total there are 3 people who apply good patient safety there are 3 people (100%). The results of the bivariate analysis obtained p value = 0.034 (<0.050), thus it can be said that there is a significant (significant) relationship between the physical workload of midwife and the application of patient safety.Conclusions and Suggestions: There is a significant (significant) relationship between the physical workload of midwife and the application of patient safety at the RSUD Kabupaten Bekasi. It is hoped that the results of this study will serve as objective information regarding the relationship between the physical workload of midwife and the application of patient safety. Midwife are expected to further improve the application of patient safety in accordance with the procedures applicable in the hospital.